Szkoła demokracji – młodzież w świecie społeczno-politycznym. Wykluczenie, czy zaniedbanie? - Brylczak, Marcin (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper attempts to show the role of young people in society and politics. It tries to approach young adults on one hand as subjects of politics with their consciousness, rights and obligations, and on the other as the objects of a wide range of social engineering, media and educational activities by politicians. Two significant phenomena concerning the young are briefly discussed, namely social capital and exclusion from political life. The latter can be interpreted either as an attempt to escape a reality that the young do not understand, or as their conscious choice and a substitute for freedom. The process of education is significantly contributed to (apart from the institutions dedicated to this purpose, such as school and family) by the media, in particular the modern media, or post-modern ones that provide a communication channel among the young, but also attract the politicians, who try to attract the attention of the young and win their support. The author concludes by saying that the social capital generated by educational institutions as well as by the ‘networks of mutual contacts’ among the young can offer the best possible protection from the processes of alienation and exclusion that constitute a threat to democracy.
The school of democracy – young people in society and politics. Exclusion or negligence?